Evaluation of photoluminescence quantum yield of monolayer WSe2 using reference dye of 3‐borylbithiophene derivative. Issue 2 (13th January 2017) - Mohamed, Nur Baizura; Wang, Feijiu; Lim, Hong En; Zhang, Wenjin; Koirala, Sandhaya; Mouri, Shinichiro; Miyauchi, Yuhei; Matsuda, Kazunari
Abstract : We studied an evaluation method of photoluminescence (PL) quantum yield of monolayer transition metal chalcogenides (TMDs) on a transparent substrate using a reference dye. A 3‐borylbithiophene derivative (C58 H49 BN2 S4 ) reference dye shows a high PL quantum yield of 36% even in the solid form and the high quantum yield is kept in a Poly(methyl methacrylate) (PMMA) matrix. Moreover, the photon energy of PL is similar to those of monolayer TMDs. These PL characteristics of the reference dye are useful for a evaluation of PL quantum yield in monolayer TMDs. The PL quantum yield of 0.18 ± 0.03% was evaluated for mechanically exfoliated monolayer WSe2 on glass substrate at room temperature.